ASPECTS OF GROUNDWATER SALINIZATION IN CRYSTALLINE AQUIFER - Ana Mônica de Britto Costa; José Geraldo de Melo; Fernando Moreira da Silva (Revista Águas Subterrâneas, 2006)
In this work is done the evaluation of the spatial and temporal behavior of the hydrochemical parameters that characterize the water salinization of the crystalline aquifer. In addition, some aspects of the origin and mechanisms of the salinization are considered. The study was carried out taking in account a hydrochemical database, resulted of physicchemical analysis of water samples from the wells drilled in the region. The datas were handled using statistics and geostatistics techniques, specifically the Kriging. It was verified the occurrence of different types of water, with salinity increasing from the east to the west. The origin of these differences is a function of the hydrologic cycle, associated with the dynamic of the atmosphere and the characteristic relief of the region that is intensified in extreme climate situation.